Parental attitudes about acquiring a dental home for preschool children: a new concept in the Arab state of Qatar - Hendaus MA; Leghrouz B; Allabwani R; Zainel A; AlHajjaji M; Siddiqui F; Alamri M; Alhammadi AH (Dove Medical Press, 2018)
Mohamed A Hendaus,1–3 Bassil Leghrouz,4 Ruba Allabwani,4 Abdelwahed Zainel,4 Mohamed AlHajjaji,4 Faisal Siddiqui,4 Mohammed Alamri,2 Ahmed H Alhammadi1–3 1Department of Pediatrics, Section of Academic General Pediatrics, Sidra Medicine, Doha, Qatar; 2Department of Pediatrics, Hamad General Corporation, Doha, Qatar; 3Department of Clinical Pediatrics, Weill Cornell Medicine, Doha, Qatar; 4Pediatric Residency Program, Hamad General Corporation, Doha, Qatar Objective: The purpose of the study was to assess parental perceptions and acceptability of a dental home for their preschool children, a new concept in the state of Qatar. Methods: A cross-sectional prospective study was conducted at Hamad Medical Corporation, in the state of Qatar. Parents of infants and children <5 years of age were offered an interview survey. Results: A total of 309 questionnaires were completed (response rate =98%). More than 90% of the participants believed that oral health and dentition affected total-body well-being. Only 18% of parents stated that their children had excellent oral health. Interestingly, more than two-thirds of children had not had a routine dentist visit in the 12 months preceding the interview. Reasons for not having such visits included long appointment times (17.4%), the perception that dental care was expensive (15.5%), the notion that deciduous teeth did not need care (9%), the impression that insurance did not cover dental procedures (8%), unawareness of location of dental centers (4%), the child did not want to go (4%), the notion that children are difficult to handle during a dental procedure (3%), a combination of these factors (33.5%), and other factors (5%). When asked what factors would encourage them to enrol a dental home for their children, almost 20% mentioned speedy appointments followed by dentists specialized in pediatrics (14.3%), child-friendly atmosphere (12%), low cost (12%), close to home (5.7%), none (2.7%), others (2%), and all of the above (32.3%). Conclusion: Counseling by primary-care physicians can increase dental home acceptability in the state of Qatar, especially that access to health care is easy in our community. Keywords: dental home, oral health, Qatar